Beyond belief: playing with pagan spirituality in world of warcraft - Aupers, Stef (Online - Heidelberg journal of religions on the internet, 2015)
Popular online computer games, like World of Warcraft, are full-fledged virtual worlds brimming with ancient religious narratives, mystical worldviews and magical powers. Nevertheless, they are rarely discussed in sociological debates about religion. Online gaming may temporarily invoke a ‘willing suspension of disbelief’ but it can, given the fictitious nature of the text, never counter the secularization or disenchantment of Western culture. In this essay it is argued that the emphasis on (dis)belief in sociology creates a blind spot for ‘play’ as an important epistemological strategy to engage with religion. The ambivalent and transgressive nature of play, it is demonstrated, provides the opportunity for young players of World of Warcraft to experience spirituality without necessarily believing in supernatural claims; to fully immerse themselves in the ‘magic circle’ without conversion to a pre-defined set of beliefs and to freely experiment with religious narratives without becoming a true believer.